Screening Oat Genotypes for Tolerance to Salinity and Alkalinity - Bai, Jianhui; Yan, Weikai; Wang, Yuqing; Yin, Qiang; Liu, Jinghui; Wight, Charlene; Ma, Baoluo (Frontiers in Plant Science, 2018)
This study aimed to develop an effective method for determining salt and alkali tolerances in oats, an important food crop. 1) In experiment 1, 68.5mmol.L-1 salt and 22.5mmol.L-1 alkali were identified as appropriate concentrations for determining the tolerance of oats to salinity and alkalinity during germination. 2) To validate the screening method obtained in experiment 1 for use in the germination stage, 248 oat genotypes were evaluated, of which 21 were identified to be tolerant to salinity and alkalinity. 3) In experiment 3, one salt treatment (40L of Na2SO4:NaCl (1:1), 150mmol.L-1) was found to be optimal for determining the tolerance of oats to salinity during the growth and development stage. For alkalinity tolerance, the optimal treatment was 40L of Na2CO3:NaHCO3 (1:1), 75mmol.L-1. 4) Because there was no significant relationship between tolerances at the germination and growth stages, it is essential to use screening methods that combine the two stages. 5) In experiment 4, 25 oat genotypes that were highly tolerant to salinity and alkalinity at both the germination and growth stages were identified from 262 oat genotypes. 6) GGE biplot software was found to be an effective tool for interpreting the results. The plastic cone-tainer planting method was found to improve screening efficiency. 7) There were differences in the effects of salinity and alkalinity on oats. Alkali stress mainly reduces the chlorophyll content, while salinity mainly disrupts water absorption. 8) Chlorophyll content could be used as a physiological criterion for identifying both salt and alkali tolerances.